안구반응분석기를 이용한 원추각막의 생체역학인자 비교연구 - 전혜신; Hye Shin Jeon; 이종수; Jong Soo Lee (Daihan angwa haghoi jabji, 2013)
목적: 안구반응분석기로 측정한 생체역학 인자를 분석하여 원추각막에서의 특성을 알아보고자 하였다. 대상과 방법: 정상인, 원추각막의증, 및 원추각막 총 72명을 3군으로 나누어 환자의 성별, 나이, 시력을 조사하였고, 세극등현미경, Pentacam 및 안구반응분석기를 시행하여 평균 각막굴절력과 중심각막두께 및 이력현상(corneal hysteresis, CH), 저항인자(corneal resistance factor, CRF)를 측정하여 비교하였다. 결과: 모든 군은 각각 24안으로 원추각막의 평균 나이는 23.83세, 원추각막의증은 26.00세, 그리고 정상 대조군은 26.13세로 나이와 성별에서는 유의한 차이가 없었다. 평균 각막굴절력은 원추각막에서 49.87D, 원추각막의증에서 45.28D, 정상 대조군에서는 42.34D로 원추각막 혹은 원추각막의증과 정상 대조군 사이에서는 유의한 차이를 보였다(p＜0.001, p=0.001). 평균 중심각막두께는 세 군 간에 모두 유의한 차이가 있었다(p＜0.05). CH는 원추각막에서는 원추각막의증(p=0.025)과 정상 대조군(p=0.005)에 비해 유의하게 낮은 수치를 보였고, CRF는 세 군에서 모두 유의한 차이를 보였다(p＜0.05). CH와 CRF는 평균 각막굴절력과는 음의 상관관계를, 중심각막 두께와는 양의 상관관계를 보였다. 결론: 원추각막에서 CH와 CRF는 정상인과 달리 측정되며, 평균 각막굴절력과 각막두께와 연관성이 있다. 특히 원추막의증과 정상인을 감별하는 진단에는 CRF가 유용하게 사용될 수 있을 것으로 생각한다. <대한안과학회지 2013; 54(6):869-876> Purpose: To compare the biomechanical properties of keratoconus, keratoconus suspect, and normal subjects measured by ocular response analyzer. Methods: A total of 72 patients were divided into 3 groups: keratoconus, suspected keratoconus, and normal control subjects. The 3 age-matched groups were evaluated according to age, sex, and visual acuity. Slit lamp examinations, Pentacam, and ocular response analyzer (ORA) examinations were performed. Mean corneal refractive power, central corneal thickness, corneal hysteresis (CH), and corneal resistance factor (CRF) were evaluated and analyzed. Results: Twenty-four eyes were included in each group. The mean age was 23.8 years in keratoconus, 26.0 years in suspected keratoconus and 26.1 years in normal subject groups. Mean corneal refractive power was significantly higher in keratoconus (p < 0.001) and suspected keratoconus (p = 0.001) groups than in the normal subject group. Mean central corneal thickness showed significant differences among the 3 groups (p < 0.05). CH was significantly lower in keratoconus than suspected keratoconus (p = 0.025) and normal subject groups (p = 0.005), but showed no significant difference between suspected keratoconus and normal subject groups. CRF showed significant differences among all 3 groups (p < 0.05). CH and CRF had negative correlations with mean corneal refractive power and positive correlations with central corneal thickness. Conclusions: CH and CRF measured by ORA were significantly different between keratoconus and normal subject groups and had significant correlations with mean corneal refractive power and central corneal thickness. CRF may be a useful method to differentiate between suspected keratoconus and normal cornea patients. J Korean Ophthalmol Soc 2013; 54(6):869-876